Assessment of quality of three marine benthic habitat types in northern Baltic Sea. (February 2017) - Torn, Kaire; Herkül, Kristjan; Martin, Georg; Oganjan, Katarina
Highlights: Assessment system of the quality of marine habitat types reefs, sandbanks, mudflats was developed. The distribution of the three benthic habitats types in the Estonian sea areas is presented. The three surveyed habitat types were found to be in a favourable quality status. Abstract: The European Union Habitats Directive (HD) obliges member states to assess the conservation status of marine habitat types but no explicit methodologies for assessing the quality of habitats have been stated in the directive or accompanying documents. In this study, a system was developed to assess the structure and functioning of three important marine habitat types in the Estonian sea area: sandbanks (HD code 1110), mudflats (1140), and reefs (1170). The assessment system includes a list of ecological criteria and favourable reference values together with procedural rules and field sampling locations. The habitat types listed in the HD are broadly defined and may encompass different communities depending upon distinct environmental gradients. By considering these environmental gradients the habitat types reefs and sandbanks were zoned and the assessment criteria and corresponding favourable reference values were defined separately for each zone. A set of several metrics like benthos indices, community variables, presence of sensitive or typical species, proportions of functional or taxonomic groups were tested as potential criteria for determining habitat quality. The most appropriate criteria were selected for incorporation into the assessment system based on ecological eligibility, suitability to local conditions, occurrence rates of benthic species, responses to disturbances, statistical properties of distribution of measured values, and practical considerations. Extensive benthos database (records from the whole Estonian sea area, 1995–2014) was used to calculate values of criteria to support the selection of criteria and to derive reference values. In order to fully take into account their crucial role in maintaining the structure and functioning of habitats, the criteria on habitat-forming species were assigned higher hierarchical order in the assessment scheme compared to other criteria. Special field works were carried out to assess the status of the three habitat types in 2015. The quality of all three monitored habitats was assessed to be in a favourable status. Additionally, the distributions of the three habitat types were mapped. To date, this is the first study in the Baltic Sea region that formulates HD compliant explicit criteria, reference values, and assessment procedures for several marine habitat types. The main challenges of the study were to derive assessment criteria and favourable reference values that are ecologically relevant and practically feasible.